THE INHIBITING EFFECT OF FS-1 DRUG ON THE ANTIOXIDANT PROTECTION SYSTEM OF MYCOBACTERIA TUBERCULOSIS - Kerimzhanova B. F.; Dzhumagazieva A.B.; Аkhatullina N. B.; Iskakbayeva Zh. A.; Sakhipov E. N. (Academic Scientific Journal of Chemistry, 2020)
Results of inhibitory action of FS-1 drug on antioxidant system of pathogenic mycobacteria tuberculosis, including resistant MDR strain, are presented. The study of the effect of FS-1 drug on the activity of the antioxidant system was carried out on the reference strain Mycobacterium tuberculosis H37Rv and MDR (rifampicin, isoniazid, streptomycin, ethambutol, еthionamide, kanamycin, cycloserine and pyrazinamide resistant) strain Mycobacterium tuberculosis 320. FS-1 drug under experimental conditions in vitro showed a new mechanism of action on mycobacteria tuberculosis - suppression of functional activity of the enzyme superoxide dismutase, which protects the microorganism from oxidative stress. The loss of resistance to oxidative stress by a bacterial cell, i.e. the ability to neutralize highly toxic oxygen radicals, leads to the destruction of cellular structures, metabolic and energy processes, disruption of the respiratory system and, as a result, its death. Antioxidant activity of Mycobacterium tuberculosis H37Rv after exposure with FS-1 preparation at concentrations of 4µg/ml is inhibited by 90.64 %, while at concentration of 2 µg/ml on bacterial culture of this strain - by 89.07 %. The obtained results show significant suppression of functional activity of superoxide dismutase enzyme in bacterial culture of Mycobacterium tuberculosis H37Rv under the influence of FS-1 in these concentrations, showing pronounced inhibitory effect. Similar studies of the effect of iodine-containing FS-1 drug on the antioxidant system were carried out on the bacterial culture of M. tuberculosis multidrug resistant strain 320. It was found that antioxidant activity of FS-1 preparation in concentration 4 µg/ml is inhibited by 99 %, while in concentrations 2 µg/ml FS-1preparation suppresses antioxidant activity of strain 320 by 98 %. Thus, the studies showed that the FS-1 preparation at the test concentrations of 4 μg/ml and 2 μg/ml has a mechanism for pronounced inhibition of the functional activity of the enzyme superoxide dismutase in Mycobacterium tuberculosis of both the reference sensitive strain H37Rv and the multidrug resistant strain 320. This leads to disruption of the redox transformations of various chemical compounds that form the respiratory process in the bacterial culture, providing the energy demand of the microorganism.